(untitled) (Czech Journal of Multidisciplinary Innovations, 2025)
A comparison of information found in sources from different periods regarding the belief system of the Saba’ia (الصابئون (shows that there are often conflicting views about them. For this reason, contemporary scholars of religion and Islamic studies also have varying understandings of the Sabaeans. In the two surviving works of Imam Maturidi related to tafsir and Islamic creed, information about this belief system is available. A comparative analysis of these references helps to clarify the complex concepts surrounding the Saba’ia doctrine